(untitled) (Global Journal of Science Frontier Research, 2020)
Crop production in sub Saharan Africa is threatened by several constraints including damage by insect and mite pests and diseases. Use of synthetic pesticides is preferred in most situations the world over. However, these have negative effects on the environment; the insect pest themselves as well as on humans. A study into the evaluation of lantana (Lantana camara) leaves and roots for the control of cowpea insect pests was carried out as a field experiment at Cotton Research Institute, Sanyati District, Zimbabwe. The experiment was laid out as a Randomized Complete Block Design with six treatments replicated three times. The treatments comprised of lantana leaves and roots at 50g/l, and 75g/l each, an uncontrolled treatment and Dimethoate 40 EC at 2.5 ml/l. Effects of these treatments on aphids (Aphis craccivora), pod borer (Maruca vitrata) and foliage beetle (Ootheca mutabilis) counts and damage and grain yield were determined. The data was analyzed using Genstat 14th edition and means were separated using Duncan’s Multiple Range Test. The results of the study showed that lantana leaf and root extracts significantly (P˂0.001) reduced A. craccivora, O. mutabilis, and M. vitrata populations at 75g/l.